Analisis Dampak Sinetron “Jangan Bercerai Bunda” Terhadap Pembentukan Moralitas Publik - Novita, Zahra Ersyah; Az Zahra, Shabrina Najla; Desrina, Rania Adriane; Ramadhanti, Shaila Azalea; Manurung, Abraham Hadonganan; Rahman, Hafizh Aulia; Marpaung, Haezer Josua Tio; Fauziyyah, Laila; Febriza, Muhammad Dyo; Sinulingga, Rizki Hagina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to analyze the impact of the television drama “Jangan Bercerai Bunda”, specifically episodes 491, 511, and 345, on the formation of public morality. These particular episodes were selected due to their portrayal of complex domestic conflicts, intense emotional dynamics, and varied representations of moral values. Using a qualitative approach through content analysis and focused interviews, this research explores how certain scenes influence viewers’ perceptions of values such as loyalty, family responsibility, gender roles, and conflict resolution. The findings indicate that the drama plays a dual role: it can deliver positive moral messages about the importance of communication and family resilience, yet it may also shape misleading perceptions if conflicts are portrayed excessively or unrealistically. In conclusion, television dramas, as a form of popular media, significantly contribute to the construction of public morality and should be critically evaluated by both audiences and content creators.